A general framework for animal density estimation from acoustic detections across a fixed microphone array. Issue 1 (16th November 2014) - Stevenson, Ben C.; Borchers, David L.; Altwegg, Res; Swift, René J.; Gillespie, Douglas M.; Measey, G. John; Freckleton, Robert
Summary Acoustic monitoring can be an efficient, cheap, non‐invasive alternative to physical trapping of individuals. Spatially explicit capture–recapture (SECR) methods have been proposed to estimate calling animal abundance and density from data collected by a fixed array of microphones. However, these methods make some assumptions that are unlikely to hold in many situations, and the consequences of violating these are yet to be investigated. We generalize existing acoustic SECR methodology, enabling these methods to be used in a much wider variety of situations. We incorporate time‐of‐arrival (TOA) data collected by the microphone array, increasing the precision of calling animal density estimates. We use our method to estimate calling male density of the Cape Peninsula Moss Frog Arthroleptella lightfooti. Our method gives rise to an estimator of calling animal density that has negligible bias, and 95% confidence intervals with appropriate coverage. We show that using TOA information can substantially improve estimate precision. Our analysis of the A. lightfooti data provides the first statistically rigorous estimate of calling male density for an anuran population using a microphone array. This method fills a methodological gap in the monitoring of frog populations and is applicable to acoustic monitoring of other species that call or vocalize.